Development of Hybrid-Based Rotemz Teaching Media in Science Learning to Increase Learning Interest of Elementary School Students - Lutfauziah, Asmaul; Retikasari, Frysca Virnanda; Rahmawati, Dewi; Arum, Dian Famila; Fitriyah, Fifi Khoirul (Jurnal Pendidikan Anak, 2024)
This research aims to develop and evaluate the hybrid-based learning media "Rotemz" in elementaryschools, especially to foster students’ interest in learning. Currently, hybrid-based learning media is stillrarely available in elementary schools. The research method used is research and development. Thedevelopment of this teaching media was carried out based on an analysis of the needs of grade 4 studentsusing the 4D development model. The development procedure includes the Define, Design and Developstages. Media validation is carried out by involving media experts, natural science material experts, andpractitioners. The validation results are used as a basis for improving learning media. This teaching mediawas implemented at SDN Ketintang II Surabaya involving 30 grade 4 students. The effectiveness of themedia in fostering students’ interest in learning was evaluated using a questionnaire filled in by teachers andstudents after the learning process. The research results show that Rotemz teaching media obtained verygood validation results based on several important aspects such as media appearance, material durability,language, suitability to learning objectives, and concept correctness. Rotemz teaching media is very suitablefor use in learning in fourth grade elementary schools. The use of this media has succeeded in growingstudents’ interest in learning and helping overcome students’ learning concentration problems. Rotemzteaching media is different from existing learning media because this media is hybrid and 3-dimensionalbased with a focus on natural resource material.